Association between the triglyceride–glucose index and left atrial appendage thrombogenic milieu in patients with atrial fibrillation - Sun, Hanze; Hu, Shuangzheng; Pan, Rongrong; Zhuang, Qin; Zheng, Yi (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesThe triglyceride–glucose (TyG) index is an independent predictor of atrial fibrillation (AF). The presence of left atrial appendage (LAA) thrombogenic milieu (LAATM) is associated with ischemic stroke in patients with AF. The present study aimed to explore the relationship between the TyG index and LAATM in patients with AF.MethodsPatients with nonvalvular AF who were admitted to the Department of Cardiology at Cixi People Hospital Medical Health Group for catheter ablation or LAA closure from April 2018 to January 2024 were retrospectively included. The study population was divided into two groups on the basis of the presence (LAATM group) or absence (non-LAATM group) of LAATM as determined by preprocedural transesophageal echocardiography. The relationship between the TyG index and LAATM was observed.ResultsA total of 466 patients with nonvalvular AF who underwent transesophageal echocardiography (TEE) examination were included. LAATM was observed in 62 (13.3%) patients. The TyG index was higher in patients with LAATM (7.56 ± 0.59 vs. 7.04 ± 0.47, P < 0.001). Multivariate logistic analysis demonstrated that higher TyG index was an independent predictor of LAATM development (odds ratio = 12.78, 95% confidence interval 2.95–55.42; P < 0.001). Receiver operating characteristic curve analysis revealed that the optimal cutoff value of the TyG index for predicting LAATM development was 7.01 (area under the curve: 0.76; sensitivity 93.5%, specificity 50.2%).ConclusionThe TyG index, which is calculated on the basis of triglyceride and fasting plasma glucose levels, was positively associated with LAATM development in patients with AF.